2012
DOI: 10.1089/ten.tea.2011.0569
|View full text |Cite
|
Sign up to set email alerts
|

Regeneration of Native-Like Neo-Urinary Tissue from Nonbladder Cell Sources

Abstract: Urinary pathology requiring urinary diversion, partial or full bladder replacement, is a significant clinical problem affecting ~14,000 individuals annually in the United States alone. The use of gastrointestinal tissue for urinary diversion or bladder reconstruction/replacement surgeries is frequently associated with complications. To try and alleviate or reduce the frequency of these complications, tissue engineering and regenerative medicine strategies have been developed using bio-absorbable materials seed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 42 publications
0
29
0
Order By: Relevance
“…Moreover, their isolation, as well as their method of culture, is well established and described liberally in the literature 101,102. However, their use may not be proper in some diseases 103. Also, harvesting cells from patients with urothelial carcinomas carries the risk of tumor recurrence 104.…”
Section: Biofabrication Of the Urinary Tractmentioning
confidence: 99%
“…Moreover, their isolation, as well as their method of culture, is well established and described liberally in the literature 101,102. However, their use may not be proper in some diseases 103. Also, harvesting cells from patients with urothelial carcinomas carries the risk of tumor recurrence 104.…”
Section: Biofabrication Of the Urinary Tractmentioning
confidence: 99%
“…Obtained results showed that the use of smooth muscle cells from different origins led to regeneration of a neo-organ resembling native bladder tissue composed of urothelium and smooth muscle layers. The use of acellular scaffold resulted in fibrous connective tissue development with a small number of smooth muscle cells [21]. Another study was performed on 30 rabbits using bladder acellular matrix (BAM).…”
Section: Current Attempts In Artificial Conduit Constructionmentioning
confidence: 99%
“…Dorin et al regenerated the urethra using acellular [19,20,24]. B -two ureters were anastomosed with artificial conduit; urinary bladder was removed [21,22,23].…”
Section: Future Perspectivesmentioning
confidence: 99%
“…They are commonly harvested by bladder biopsy in humans and by bladder digestion in animal studies [28,32,[57][58][59]. In order to avoid a urinary source, SMCs have also been isolated from other tissues including adipose and peripheral blood [60]. In addition, as mentioned earlier, SMCs have been derived from other cells, notably MSCs [17,61 && ,62,63].…”
Section: Smooth Muscle Cellsmentioning
confidence: 99%